2009
DOI: 10.1074/jbc.m109.052928
|View full text |Cite
|
Sign up to set email alerts
|

The Lysine 48 and Lysine 63 Ubiquitin Conjugates Are Processed Differently by the 26 S Proteasome

Abstract: The role of Lys-63 ubiquitin chains in targeting proteins for proteasomal degradation is still obscure. We systematically compared proteasomal processing of Lys-63 ubiquitin chains with that of the canonical proteolytic signal, Lys-48 ubiquitin chains. Quantitative mass spectrometric analysis of ubiquitin chains in HeLa cells determines that the levels of Lys-63 ubiquitin chains are insensitive to short-time proteasome inhibition. Also, the Lys-48/Lys-63 ratio in the 26 S proteasome-bound fraction is 1.7-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
133
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 47 publications
4
133
0
Order By: Relevance
“…5C). USP5 and UCH37 are known to deubiquitinate both K48-and K63-linked polyubiquitinated proteins (50,51). The accumulation of K63-linked polyubiquitinated proteins in WP1130-treated HEK293T cells may partially be explained based on these findings, although there are other DUBs, such as CYLD (51), which can break such chains as well.…”
Section: Discussionmentioning
confidence: 78%
“…5C). USP5 and UCH37 are known to deubiquitinate both K48-and K63-linked polyubiquitinated proteins (50,51). The accumulation of K63-linked polyubiquitinated proteins in WP1130-treated HEK293T cells may partially be explained based on these findings, although there are other DUBs, such as CYLD (51), which can break such chains as well.…”
Section: Discussionmentioning
confidence: 78%
“…Although Ub is a canonical degradation signal, both Ub-48 Ub and Ub-63 Ub are hydrolyzed by purified proteasomes in vitro (16,17), and some studies have observed Ub-63 Ub specificity in the polyUb amputation activity of Poh1 (18,19). Whether Ub-63 Ub has a role at the proteasome remains unclear; its presence at this location would seem incongruous with a model in which only Ub-48 Ublabeled proteins are genuine substrates (20,21).…”
mentioning
confidence: 79%
“…1). Of the three DUBs associated with the proteasome 19S RP, Poh1 uniquely cleaves an isopeptide bond between the proximal Ub in a polyUb adduct and its substrate, thereby releasing a polyUb chain en bloc (16,25,26). To test the notion that Poh1 might deubiquitinate TRIM21, we stably depleted Poh1 in TE671 cells by shRNA expression, assessing efficiency by immunoblot (Fig.…”
Section: Ube2w and Ube2n Are Required For Trim21 Dual Effector And Sementioning
confidence: 99%
“…It was originally suggested that the chain trimming activity serves as a safeguard to rescue poorly ubiquitinated proteins from the proteasome by editing the conjugates (6). We recently found that Lys-63 polyUb chains are highly susceptible to chain trimming, which renders Lys-63-linked polyUb conjugates to be rapidly deubiquitinated by the 26 S proteasome without efficient degradation (11). Thus, Ub chain trimming could rescue Lys-63-linked substrates from proteasomal degradation.…”
mentioning
confidence: 99%